The effect of combined hormonal contraceptives use on brain reactivity during response inhibition. (3rd March 2016) - Gingnell, Malin; Bannbers, Elin; Engman, Jonas; Frick, Andreas; Moby, Lena; Wikström, Johan; Sundström-Poromaa, Inger
Abstract : Objectives Cognitive control, which can be described as the ability to moderate impulses, has not previously been investigated in users of combined hormonal contraception (CHC). Given the suggested modulatory role of ovarian steroids in prefrontal dopaminergic function, which in turn taps into cognitive control, this randomised, double-blinded, placebo-controlled oral contraceptive trial set out to investigate the brain activity pattern during response inhibition in CHC users. Methods Thirty-four women were randomised to one treatment cycle with a levonorgestrel-containing CHC or placebo. The women performed a Go/NoGo task to measure brain activity during response inhibition by use of event-related functional magnetic resonance imaging (fMRI) prior to and during the CHC/placebo treatment cycle. Results No differences between CHC and placebo users in number of correct inhibitions were found during treatment, but only women on CHC significantly improved their performance between the baseline and treatment assessments. During the treatment cycle CHC users displayed decreased activity in the right middle frontal gyrus in comparison with placebo users. No other significant activations were evident between treatment groups or within groups. Conclusion Overall, CHC use had marginal effects on brain activity during response inhibition. If anything, the findings of the study may suggest reduced effort or increased efficiency in maintaining orbitofrontal cortex inhibitory cognitive control when using a combined oral contraceptive.